Aortopulmonary window with anomalous ascending aortic origin of left pulmonary artery: Hitherto unreported pattern. Issue 11 (6th September 2022) - Sharma, Arun; Naganur, Sanjeev Hanumantacharya; Barwad, Parag; Singhal, Manphool
Abstract: Anomalous ascending aortic origin of left pulmonary artery in association with aortopulmonary window has not been reported so far in literature and is the main highlight of the present case.